Fabrication And Characterization Of O.5-Um Mosfet Bulk Silicon Technology On Thick Bonded Silicon-On-Insulator Substrate - Abdullah, Wan Fazlida Hanim (2003)
The effect of thick film Silicon-On-Insulator (SOl) substrate on device fabrication and performance is studied. Enhancement-type Partially-Depleted SOl MOS device is fabricated on bonded SOl (BSOI) substrate based on bulk silicon MIMOS 0.5 um CMOS technology with full compatibility maintained. The substrate employed is commercially available with the specification 1.5 um silicon device layer with ±0.5 um within wafer variation on 2 um buried oxide achieved by bonding followed by mechanical thinning .. Prior to device fabrication, sacrificial oxidation is applied to adjust the top silicon layer thickness. Throughout the fabrication, monitoring steps using spectroscopic reflectometry technique are taken in ensuring enough silicon thickness is left on the top BSOI surface for device construction. To allow comparison of substrate effects, bulk silicon substrates are included in the fabrication as control wafers.Three main electrical parameters were extracted from all sites of all the wafers. Bonded SOl (BSOI) substrate is observed to undesirably increase threshold voltage and decrease drive current capability. Sacrificial oxidation technique to adjust the silicon layer thickness worsens device performance and yield. However, BSOI substrate offers much improved off-state leakage current compared to bulk devices. Further current-voltage sweep data analysis show that BSOI substrate improves the subthreshold slope, reduces the drain-induced barrier lowering effect and improves resistance towards latchup. Peculiar device characteristics typical to Partially-Depleted SOl devices were observed from the output characteristics. These include early breakdown voltage, negative conductance in the saturation region of body-contacted devices at high gate voltages and kink effect when the body is left floating. The results show that SOl fabrication is achievable using existing bulk silicon fabrication technology. Even though devices on BSOI substrate show certain improvements in device characteristics, the full potential of the SOl structure could not be achieved with the thickness and uniformity of the BSOI substrate applied.